Novel mutations in structural proteins of dengue virus genomes - Saira Mushtaq; Malik Ihsan Ullah Khan; Muhammad Tahir Khan; Madeeha Shahzad Lodhi; Dong Qing Wei (Elsevier, 2023)
Background: Genomic characterization of the dengue virus (DENV) is useful for understanding its molecular evolution, transmission, pathogenicity and infectivity. The DENV genomic RNA encodes three structural proteins, capsid (C) envelope (E) and membrane (M) proteins mediating viral entry and assembly during host infection. The current study aims to explore the DENV serotypes and mutations in the E and M proteins. Methods: Twenty-three samples of DENV-positive patients were processed and selected for whole genome sequencing (WGS) from the Punjab Province of Pakistan. Results: Among the 23 WGS, 19 samples showed numerous mutations (BioProject ID PRJNA943555). DENV1 and DENV2 are the most prevalent serotypes. A total of 179 mutations were detected in the E protein, in which K203E, T88A, I114L, and I293T are novel. The I270L, T272A, S273L, and T277A were found in the "kl" β-hairpin (aa 270-279). The M protein harbors 74 mutations, of which 24 were novel. Three prominent complementary regions in the prM and E protein complex formations include R6, E46, D47, D63, and D65 on 'pr' peptide, and E84, K64, and H244, K247 on E, remain conserved except R6C. To our knowledge, it is the first comprehensive study of mutations in structural proteins. Conclusion: Genomic epidemiology is critical for analyzing emerging mutations and designing new policies therapeutic efforts for future outbreaks.